Pengaruh Blended Learning terhadap Kreativitas Mahasiswa Calon Guru di Universitas Negeri Medan - Siregar, Nurhasanah; Manurung, Sri Lestari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2020)
This study aims to determine the effect of blended learning strategies on the creativity of the pre-service teachers. By a quantitative approach, the type used in this study is a quasi-experimental with pretest-posttest control group design. The population in this study were pre-service teachers in semester VII of the Mathematics Education Study Program at Universitas Negeri Medan. The instrument has used a test in the form of essay tests of 5 items concerning creativity. The results of the study indicated that there were significant differences in the creativity of pre-services teachers who apply blended learning and direct learning. Thus, it could be concluded that blended learning gave effects of creativity.